Efficient and reversible CO2 capture in bio-based ionic liquids solutions. (January 2022) - Latini, Giulio; Signorile, Matteo; Rosso, Francesca; Fin, Andrea; d'Amora, Marta; Giordani, Silvia; Pirri, Fabrizio; Crocellà, Valentina; Bordiga, Silvia; Bocchini, Sergio
Graphical abstract: Innovative bio-based non-toxic ionic liquids turn out to be innovative and sustainable systems for CO2 capture and release under mild condition. Highlights: Bio based ionic liquid solution demonstrate high CO2 capture. Solvent addition increase bio based ionic liquid effectiveness. The non-toxicity of a bio based ionic liquid was demonstrated. Abstract: Choline/amino acid-based ionic liquids were synthetized via ionic metathesis and their CO2 absorption performances evaluated by employing different experimental approaches. In order to overcome any viscosity-related problem, dimethyl sulfoxide (DMSO) was employed as solvent. IL-DMSO solutions with different IL concentrations were evaluated as absorbents for CO2, also investigating their good cyclability as desirable for real industrial CO2 capture technologies. 1 H-NMR and in-situ ATR-IR experiments were the toolbox to study the CO2 chemical fixation mechanism under different experimental conditions, proving the formation of distinct chemical species (carbamic acid and/or ammonium carbamate). In general, these ILs demonstrated molar uptakes higher than classical 0.5 mol CO2 /mol IL and the capacity to release CO2 in extremely mild conditions. The possible biological adverse effects were also analyzed, for the first time, in zebrafish ( Danio rerio ) during the development, by assessing for different toxicological endpoints, proving the non-toxicity and high biocompatibility of these bio-inspired ILs.